Microbial community changes along the active seepage site of one cold seep in the Red Sea - Cao, Huiluo; Zhang, Weipeng; Wang, Yong; Qian, Pei-Yuan (Frontiers in Microbiology, 2015)
The active seepage of the marine cold seeps could be a critical process for the exchange of energy between the submerged geosphere and the sea floor environment through organic-rich fluids, potentially even affecting surrounding microbial habitats. However, few studies have investigated the associated microbial community changes. In the present study, 16S rRNA genes were pyrosequenced to decipher changes in the microbial communities from the Thuwal seepage point in the Red Sea to nearby marine sediments in the brine pool, normal marine sediments and water, and benthic microbial mats. An unexpected number of reads from unclassified groups were detected in these habitats; however, the ecological functions of these groups remain unresolved. Furthermore, ammonia-oxidizing archaeal community structures were investigated using the ammonia monooxygenase subunit A (amoA) gene. Analysis of amoA showed that planktonic marine habitats, including seeps and marine water, hosted archaeal ammonia oxidizers that differed from those in microbial mats and marine sediments, suggesting modifications of the ammonia oxidizing archaeal communities along the environmental gradient from active seepage sites to peripheral areas. Changes in the microbial community structure of ammonia oxidizing archaea in different habitats (water versus sediment) potentially correlated with changes in salinity and oxygen concentrations. Overall, the present results revealed for the first time unanticipated novel microbial groups and changes in the ammonia-oxidizing archaea in response to environmental gradients near the active seepages of a cold seep.